2015
DOI: 10.1371/journal.pone.0128945
|View full text |Cite
|
Sign up to set email alerts
|

Redundancy between Cysteine Cathepsins in Murine Experimental Autoimmune Encephalomyelitis

Abstract: The cysteine cathepsins B, S, and L are functionally linked to antigen processing, and hence to autoimmune disorders such as multiple sclerosis. Stemming from several studies that demonstrate that mice can be protected from experimental autoimmune encephalomyelitis (EAE) through the pharmacologic inhibition of cysteine cathepsins, it has been suggested that targeting these enzymes in multiple sclerosis may be of therapeutic benefit. Utilizing mice deficient in cysteine cathepsins both individually and in combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…Concomitantly, the degree of compensation by the different cathepsins for the cleavage of the VC linker can also vary. For example, we found that immune (27)(28)(29). Dubowchik and colleagues posited that other enzymes in liver extracts might contribute to the faster digestion rate observed with lysosomal extracts versus purified cathepsin B (7).…”
Section: Discussionmentioning
confidence: 88%
“…Concomitantly, the degree of compensation by the different cathepsins for the cleavage of the VC linker can also vary. For example, we found that immune (27)(28)(29). Dubowchik and colleagues posited that other enzymes in liver extracts might contribute to the faster digestion rate observed with lysosomal extracts versus purified cathepsin B (7).…”
Section: Discussionmentioning
confidence: 88%
“…Anatomically, EAE‐affected brains were found to be highly expressing CD14 in many regions such as SpC and CB . The lysosomal protein Ctss is responsible for MHC‐II processing, and knockout of Ctss leads to a lesser MHC‐II expression and MOG antigen presentation, in addition to protection from EAE . Hexb functions as a glycosyl hydrolase inside the lysosome and its dysfunction leads to neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It is to be noted here that several isoforms of cathepsin L have also been observed in specific cell types due to alternative splicing of mRNA transcripts and alternative translation [4,[37][38][39][40][41].Molecules 2020, 25, 698 2 of 40 variety of highly invasive forms of cancer is also now well established and has been a subject of elegant reviews elsewhere [25][26][27]. Unfortunately, several overlapping and redundant functions of cathepsin L have also emerged [5,[28][29][30]. It is therefore critically important that its functional biology in both normal and disease-specific cell types be clearly annotated before significant resources are directed in drug discovery endeavors.…”
mentioning
confidence: 95%
“…This review elaborates on the recently developed small molecule inhibitors and probes of human cathepsin L, outlining their mechanisms of action, and describing their potential utilities in dissecting unknown function.Molecules 2020, 25, 698 2 of 41 also now well established and has been a subject of elegant reviews elsewhere [25][26][27]. Unfortunately, several overlapping and redundant functions of cathepsin L have also emerged [5,[28][29][30]. It is therefore critically important that its functional biology in both normal and disease-specific cell types be clearly annotated before significant resources are directed in drug discovery endeavors.…”
mentioning
confidence: 99%